Practice-based Research Networks (PBRNs): Meeting the Challenges of the Future - Calmbach, Walter L. (2012)
Practice-based research networks (PBRNs) are useful tools for conducting studies in the busy primary care setting, but their continued existence is threatened by a range of challenges. PBRNs must position themselves now to be prepared to face the challenges ahead. For example, experience with the Clinical Translational Science Awards has placed PBRNs at the center of university efforts toward greater community engagement. Networks must use this opportunity to solicit infrastructure support and partner with experienced principal investigators from other disciplines. Successful networks must make greater use of health information technology to solicit clinician involvement, identify and recruit potential subjects, and disseminate key findings. To maintain the active participation of busy clinicians in the clinical research enterprise, networks must find new ways to engage their members and simplify study participation. Networks should pursue clinically relevant projects that create meaning and connect busy practitioners to the larger agenda of primary care research. Finally, collaborating with other networks in a structured and ongoing manner is one way for PBRNs to extend their reach while making maximal use of their unique resources and local expertise.